Balance hídrico de la microcuenca río “Pise”, Cantón Valencia, Provincia Los Ríos - Carrascal Acosta, Zhara Gabriela (2015)
This research "Water balance of the watershed River" Pise ", Canton Valencia, province Los Rios" was conducted between July and December 2014, the objectives in this research were: To characterize the biophysical conditions influence watershed area; determine the availability of water in the "micro-Step"; determine the basic physicochemical parameters and heavy metals that may affect water quality "Step" river and develop a proposal for sustainable management of the watershed. To characterize the biophysical conditions of the watershed was based on analysis of information generated by the INAMHI, the MAGAP and GAD Provincial “Los Rios”, in addition to the journeys made in the field visit. Determining the availability of water in the watershed is performed by obtaining the mathematical modeling of precipitation and temperature, later to calculate potential evapotranspiration using temperature and precipitation variables previously calculated. For the analysis of basic physicochemical parameters and heavy metals, monitoring was conducted at three different points (upper, middle and lower) and water samples were collected for analysis in the laboratory of Soil and Water State Technical University Quevedo and the accredited testing laboratory Chemical Group Marcos city of Guayaquil; where it was found that certain parameters analyzed are outside the limits set in TULSMA and EPA